Microwave-assisted synthesis of novel Ti/BTB-MOFs as porous anticancer and antibacterial agents - Altharawi, Ali; Alqahtani, Safar M.; Aldakhil, Taibah; Ahmad, Irfan (Frontiers in Chemistry, 2024)
Nano compounds, especially metal-organic frameworks (MOFs), have significant properties. Among the most important properties of these compounds, which depend on their specific surface area and porosity, are biological properties, such as anticancer and antibacterial properties. In this study, a new titanium/BTB metal-organic framework (Ti/BTB-MOF) was synthesized by using titanium nitrate and 1,3,5-Tris(4-carboxyphenyl)benzene (BTB) under microwave radiation. The structure of the synthesized Ti/BTB-MOF was characterized and confirmed using X-ray diffraction (XRD) patterns, X-ray photoelectron spectroscopy (XPS) analysis, Fourier transform infrared (FT-IR) spectra, energy-dispersive X-ray (EDAX) analysis mapping, scanning electron microscope (SEM) images, thermogravimetric analysis (TGA) curves, and Brunauer–Emmett–Teller (BET) analysis. The in vitro anticancer properties of Ti/BTB-MOF were evaluated using the MTT method against MG-63/bone cancer cells and A-431/skin cancer cells. The in vitro antibacterial activity was tested using the Clinical and Laboratory Standards Institute (CLSI) guidelines. In the anticancer activity, IC50 (half-maximal inhibitory concentration) values of 152 μg/mL and 201 μg/mL for MG-63/bone cancer cells and A-431/skin cancer cells, respectively, were observed. In the antibacterial activity, minimum inhibitory concentrations (MICs) of 2–64 μg/mL were observed against studied pathogenic strains. The antimicrobial activity of Ti/BTB-MOF was higher than that of penicillin and gentamicin. Therefore, the synthesized Ti/BTB-MOF could be introduced as a suitable bioactive candidate.